Исследование процесса восстановления стационарного режима генерации CuBr-лазера; Оптика атмосферы и океана; Т. 30, № 3 - Васнев Н. А. Николай Александрович; Тригуб М. В. Максим Викторович; Троицкий В. О. Владимир Олегович; Димаки В. А. Виктор Анатольевич; Власов В. В. Василий Васильевич (2017, 2017)
Заглавие с экрана